The Effect of Dormitory-Based Coaching and Religiosity on Islamic Education Learning Outcomes - Marzuki; Yusuff Olatunji Abimbowo; Chanda Chansa Thelma (Al-Qalam Institute, 2024)
This study investigates the influence of dormitory-based coaching and religiosity on the learning outcomes of Islamic education students. The research explores the relationship between these variables and their combined effect on academic performance. A quantitative approach using a correlational research design was employed, with a sample of 150 students from SMP Islam Darul Ulum Bantaran. Data was collected through a standardized questionnaire assessing dormitory coaching, religiosity, and academic performance, with analysis conducted using multiple linear regression and correlation techniques. The findings reveal that dormitory-based coaching (p = 0.042) and religiosity (p = 0.000) significantly positively impact learning outcomes. Furthermore, the study demonstrates a strong interaction between the two factors, suggesting that students who experience high levels of coaching and religiosity tend to achieve the best academic results. These results highlight the importance of integrating dormitory-based coaching and strengthening religiosity in educational settings. This research contributes to developing a holistic educational approach and provides valuable insights for improving educational practices, particularly in Islamic schools. Future research may explore additional factors influencing learning outcomes and assess the long-term effects of these variables on student development.